History of Collage : An anthology of collage, assemblage and event structures. - Wolfram, Eddie (London : Studio Vista, 1975)
Albers, Josef ; Alloway, Lawrence ; Altman, Natan ; Amaya, Mario ; Andersen, Hans Christian ; Andre, Carl ; Andreenko, Michel ; Annenkoy, Georges ; Aragon, Louis ; Archipenko, Alexander ; Ardon, Mordechai ; Arenas, B. Raulio ; Arensberg, Walter ; Arp, Hans (Jean) ; Baader, Johannes ; Baargeld, Johannes Theodor ; Baj, Enrico ; Ball, Hugo ; Balla, Giacomo ; Banham, P. Reyner ; Banting, John ; Baranoff-Rossine, Wladimir ; Bardi, P.M. ; Barker, Clive ; Barnes, Albert ; Barta, Alexander ; Baumeister, Willi ; Bayer, Herbert ; Baziotes, William ; Beardsley, Aubrey ; Beckmann, Max ; Bellmer, Hans ; Bergmann-Michel, Ella ; Berlewi, Henryk ; Berry, John ; Beuys, Joseph ; Biederman, Charles ; Bierke-Peterson, Vilhelm ; Bill, Max ; Bille, Eiler ; Blake, Peter ; Blumenfeld, Erwin ; Boccioni, Umberto ; Bogoslavskaya, Xenia ; Bolotowsky, Ilya ; Bonnard, Pierre ; Bontecou, Lee ; Bortnyik, Sándor ; Boumeester, Christine ; Bragaglia, Anton Giulio ; Brancusi, Constantin ; Braque, Georges ; Brauner, Victor ; Breton, André ; Brignoni, Serge ; Brik, Lilya ; Brisley, Stuart ; Bronstein, Max ; Bruni, Lev ; Brunius, J.B. ; Bryen, Camille ; Bucheister, Carl ; Bunuel, Luis ; Burchartz, Max ; Burljuk, David ; Burra, Edward ; Burri, Alberto ; Burt, Laurence ; Bury, Pol ; Butler, Reg ; Cáceres, Jorge ; Cage, John ; Calder, Alexander ; Cangiullo, Francesco ; Caro, Anthony ; Carrà, Carlo ; Carrington, Leonora ; Cassirer, Bruno ; Cendrars, Blaise ; César ; Cézanne, Paul ; Chadwick, Lynn ; Chagall, Marc ; Chamberlain, John ; De Chirico, Giorgio ; Christo ; Citroen, Hans ; Citroen, Paul ; Clatworthy, Robert ; Cocteau, Jean ; Conti, Primo ; Coppel, Jean ; Coppel, Jeanne ; Cornell, Joseph ; Coutts-Smith, Kenneth ; Covert, John R. ; Crotti, Jean ; Cuixart, Modesto ; Dali, Salvador ; etc.
Engels
boek